Voluntary Spatial Attention has Different Effects on Voluntary and Reflexive Saccades - Stephanie K. Seidlits; Tammie Reza; Kevin A. Briand; Anne B. Sereno (The Scientific World Journal)
Although numerous studies have investigated the relationship between saccadic eye movements and spatial attention, one fundamental issue remains controversial. Some studies have suggested that spatial attention facilitates saccades, whereas others have claimed that eye movements are actually inhibited when spatial attention is engaged. However, these discrepancies may be because previous research has neglected to separate and specify the effects of attention for two distinct types of saccades, namely reflexive (stimulus-directed) and voluntary (antisaccades). The present study explored the effects of voluntary spatial attention on both voluntary and reflexive saccades. Results indicate that voluntary spatial attention has different effects on the two types of saccades. Antisaccades were always greatly facilitated following the engagement of spatial attention by symbolic cues (arrows) informing the subject where the upcoming saccade should be directed. Reflexive saccades showed little or no cueing effects and exhibited significant facilitation only when these cues were randomly intermixed with uncued trials. In addition, the present study tested the effects of fixation condition (gap, step, and overlap) on attentional modulation. Cueing effects did not vary due to fixation condition. Thus, voluntary spatial attention consistently showed different effects on voluntary and reflexive saccades, and there was no evidence in these studies that voluntary cues inhibit reflexive saccades, even in a gap paradigm.